PERAN ILMU SOSIOLOGI DALAM MEMAHAMI FENOMENA MUDIK LEBARAN TAHUN 2022 - Clarisa Julian Kale; Fiqhi Maulana Abi; Fortranica Clarissa Anggi Chasmala; Nadiva Nisa Sujarwo (Universitas Negeri Malang, 2023)
THE ROLE OF SOCIOLOGY IN UNDERSTANDING THE EID HOMECOMING PHENOMENON IN 2022Eid al-Fitr is a big celebration for muslims. The celebration is held after muslims fast for one full month in the month of Ramadan. The celebration of Eid al-Fitr or can be called lebaran, is usually celebrated with family and other relatives gathering. For urban people, most of whom are foreigners, the most awaited moment of Eid is going home. Homecoming is a tradition in which a person travels back to his hometown to celebrate Eid al-Fitr. The purpose of writing this article is to explore the relationship between the role of sociology and the lebaran homecoming phenomenon in 2022. The writing of this article uses the literature review method which is realized in the form of analyzing several journal articles. The results of writing this article are, according to sociologists, the desire of humans or individuals to gather with their extended family during important events is a basic need for humans, which of course humans will naturally have bonds with their families. Homecoming will also strengthen the organic solidarity of the community, where when people before and after the holiday are sometimes busy with their respective affairs, they can forget the relationship between each other. So it can be concluded that going home if viewed with the science of sociology is an activity in which it will encourage social interaction between individuals and the community which will also encourage the establishment of organic solidarity.Hari raya Idul Fitri merupakan perayaan besar bagi umat muslim. Perayaan tersebut dilaksanakan setelah umat muslim melakukan puasa satu bulan penuh di bulan Ramadhan. Perayaan idul fitri atau bisa disebut dengan lebaran, biasanya dirayakan dengan berkumpul keluarga dan sanak saudara lainnya. Bagi orang perkotaan yang kebanyakan dari mereka merupakan orang perantauan, momen lebaran yang ditunggu-tunggu adalah mudik. Mudik menjadi sebuah tradisi dimana seseorang melakukan perjalanan pulang ke kampung halamannya untuk merayakan hari raya Idul Fitri. Tujuan penulisan artikel ini yaitu untuk menggali hubungan antara peran ilmu sosiologi dengan adanya fenomena mudik lebaran tahun 2022. Penulisan artikel ini menggunakan metode literature review yang diwujudkan dalam bentuk penganalisisan beberapa artikel jurnal. Hasil dari penulisan artikel ini yaitu, menurut para ahli sosiolog, keinginan manusia atau individu untuk berkumpul bersama keluarga besarnya disaat acara-acara penting merupakan suatu kebutuhan dasar bagi manusia, tentu saja manusia secara alamiah akan memiliki ikatan dengan keluarganya. Mudik juga akan menguatkan solidaritas organik masyarakat ketika masyarakat sebelum dan sesudah hari raya kadang sibuk dengan urusan masing-masing yang bisa saling melupakan silaturahmi antar sesama. Sehingga dapat disimpulkan bahwa mudik jika dipandang dengan ilmu sosiologi merupakan suatu kegiatan yang didalamnya akan mendorong terjadinya interaksi sosial antar individu dan masyarakat yang juga akan mendorong terjalinnya solidaritas organik.